Age and sex-specific disability-free life expectancy in urban and rural settings of Bangladesh - Khandaker Tanveer Ahmed; Aziza Afrin; Mehedi Hasan; Sajjad Bin Sogir; Labiba Rahman; Md. Karimuzzaman; Kazi Arifur Rahman; Md. Moyazzem Hossain; Hafiz T. A. Khan (BMC, 2024)
Abstract Background Disability-free life expectancy (DFLE) has been used to gain a better understanding of the population's quality of life. Objectives The authors aimed to estimate age and sex-specific disability-free life expectancy (DFLE) for urban and rural areas of Bangladesh, as well as to investigate the differences in DFLE between males and females of urban and rural areas. Methods Data from the Bangladesh Sample Vital Statistics-2016 and the Bangladesh Household Income and Expenditure Survey (HIES)-2016 were used to calculate the disability-free life expectancy (DFLE) of urban and rural males and females in Bangladesh in 2016. The DFLE was calculated using the Sullivan method. Results With only a few exceptions, rural areas have higher mortality and disability rates than urban areas. For both males and females, statistically significant differences in DFLE were reported between urban and rural areas between the ages of birth and 39 years. In comparison to rural males and females, urban males and females had a longer life expectancy (LE), a longer disability-free life expectancy, and a higher share of life without disability. Conclusion This study illuminates stark urban-rural disparities in LE and DFLE, especially among individuals aged < 1-39 years. Gender dynamics reveal longer life expectancy but shorter disability-free life expectancy for Bangladeshi women compared to men, emphasizing the need for targeted interventions to address these pronounced health inequalities.